Experimental evaluation of cuttings displacement by the drill bit-drill string assembly in a horizontal well - Debiasi, Mateus (2021)
Not only the oil production but also the well depths have been increasing over the years in Brazil. As a consequence, new techniques and technologies have been required by the industry in order to be able to extract the high-quality oil that has been found in the pre-salt region. The wells are usually vertical, when the oil reservoir is located right under the well position, or directional, when a deviation angle is required to reach the reservoir. Considering a horizontal well, when the deviation angle is at 90 degrees from the vertical, cuttings from the rock formation deposit on the bottom of the hole, creating a cuttings bed. The removal of the drill string from the well causes interactions between the bottom hole assembly (BHA) and the cuttings bed which may increase significantly the drag loads or even hold the pipe. The objective of this work is to study the interactions between the drill string/bit set and the cuttings bed using an experimental rig developed to represent the described situation. It was developed an experimental rig, in which it is possible to control the axial displacement and rotation of the column, set different cuttings bed heights with 3 mm diameter glass spheres (2.6 kg/cm³) and use different fluids. The apparatus registers drag loads while the parameters that were varied are: displacement speed at 1 and 10 cm/s, rotational speed at 0 and 25 rpm, cuttings bed height at 23.6%, 35.7% and 50% and 64.3% of the total well height and fluid with two viscosities and densities, 1 cP and 1 g/cm³ and 65 cP and 1.2 g/cm³. It was observed that the column got stuck for 1 cm/s displacement speed at a 50% or higher cuttings bed height, without rotation and fluid viscosity 1 cP. However, the plug formation was avoided when the column rotates or at higher displacement speed. Evaluating the results, it was observed that it is possible to define a region for a critical Shields number. This number is the limit in which values above it the cuttings are carried by the fluid flow, while for values under it the fluid does not carry the particles.